Substrates with town refuse compost for ornamental plants production - Backes, Marco Antonio; Kampf, Atelene Normann (Pesquisa Agropecuaria Brasileira, 1991)
Two ornamental plant species were cultivated in greenhouse on substrates with town refuse compost (TRC). The best growth of Pilea cadierei L. was on TRC + peat, with or without sandy soil. Calliandra selloi (Spr.) Macbr. however did not present a good growth in this kind of substrate. The use of TRC resulted injury in the leaves and reduction of the plant size. These experiments brought the conclusion that it is possible to use TRC as substrate component or amendment for production of ornamental plants, since some negative characteristics of TRC are corrected.